Pengaruh Fasilitas Kerja, Kompensasi dan Motivasi Terhadap Kinerja Karyawan Pt. Harapan Sejahtera Karya Utama Sidoarjo - Aulia Rahmadhani Putri Anindita; Budi Prabowo (SEIKO : Journal of Management & Business, 2022)
Abstrak The purpose of this study was to determine and analyze the effect of work facilities, compensation and motivation on the performance of employees of PT. The Prosperous Hope of the Main Works. This type of research is a quantitative research. The population of this research is the employees of PT. The Prosperous Hope of the Main Works. The number of samples in this study were 95 employees with a population of 134 employees. The sampling technique is by means of a proportional random sampling technique by means of a lottery. The data collection method used is using questionnaires and documentation collection techniques. The results of this study indicate that various work facilities, compensation, and motivation partially affect the performance of employees of PT Harapan Sejahtera Karya Utama Sidoarjo. Facilities (X1) Compensation (X2) and Motivation (X3) have a significant effect simultaneously on the performance of employees of PT. Hope for the Prosperous Work of Sidoarjo. Kata Kunci: Work Facilities, Compensation, Motivation, Employee Performance